Photodynamic versus white light-guided treatment of non-muscle invasive bladder cancer: a study protocol for a randomised trial of clinical and cost-effectiveness. Issue 9 (3rd September 2019) - Tandogdu, Zafer; Lewis, Rebecca; Duncan, Anne; Penegar, Steven; McDonald, Alison; Vale, Luke; Shen, Jing; Kelly, John D; Pickard, Robert; N Dow, James; Ramsay, Craig; Mostafid, Hugh; et al.
Abstract : Introduction: Bladder cancer is the most frequently occurring tumour of the urinary system. Ta, T1 tumours and carcinoma in situ (CIS) are grouped as non-muscle invasive bladder cancer (NMIBC), which can be effectively treated by transurethral resection of bladder tumour (TURBT). There are limitations to the visualisation of tumours with conventional TURBT using white light illumination within the bladder. Incomplete resections occur from the failure to identify satellite lesions or the full extent of the tumour leading to recurrence and potential risk of disease progression. To improve complete resection, photodynamic diagnosis (PDD) has been proposed as a method that can enhance tumour detection and guide resection. The objective of the current research is to determine whether PDD-guided TURBT is better than conventional white light surgery and whether it is cost-effective. Methods and analysis: PHOTO is a pragmatic multicentre randomised controlled trial (open parallel group, non-masked and superiority trial) comparing the intervention of PDD-guided TURBT with standard white light resection in newly diagnosed intermediate and high risk NMIBC within the UK National Health Service setting. Clinical effectiveness is measured with time to recurrence. Cost-effectiveness is assessed within trial via the calculation of incremental cost per recurrence avoided and incremental cost per quality-adjusted life per year gained over 3 years and over long term through a modelling exercise over patients' lifetime. Ethics and dissemination: Formal ethics review was undertaken with a favourable opinion, in line with UK regulatory procedures (REC reference number: 14/NE/1062). If reductions in time to recurrence is associated with long-term patient benefits, the cost-effectiveness evaluation will provide further evidence to inform adoption of the technology. Findings will be shared in lay media such as patient and charity forums and will be presented at key meetings and published in academic literature. Trial registration number ISRCTN84013636 .